La innovación tecnológica y su impacto en los emprendimientos sociales en el cantón Quevedo, año 2023 - Espinosa Vera, Alex Julian (2023)
The present research aims to assess the impact of technological innovation on social entrepreneurship in the Quevedo canton. To achieve this, field and descriptive research methods were employed, utilizing both inductive and deductive approaches. The study population included 125 social entrepreneurs, and data collection was carried out through surveys, interviews, and direct observation. The results revealed that success in social entrepreneurship, concerning technological innovation, is grounded in the principles of sustainability, significance, and feasibility, encompassing both social and operational aspects. However, significant obstacles were identified, such as limited financial resources and technical knowledge, hindering the implementation of technologies in these ventures. Furthermore, it was evident that the current offering of social innovation programs is insufficient and lacks quality, emphasizing the urgent need for high-quality training programs led by competent professionals in technological innovation. In this context, it is recommended to enhance entrepreneurs' capabilities through holistic training programs and establish indicators reflecting the interrelation between social and operational outcomes. The importance of providing financial support and promoting the dissemination of training programs aligned with the real technological needs of social entrepreneurs is also emphasized. These efforts should be undertaken under the leadership of competent professionals and with mechanisms for continuous feedback to ensure sustainable and effective development in the field of technological innovation in social entrepreneurship